Perkembangan Bahasa Indonesia—Melayu di Indonesia dalam Konteks Sistem Pendidikan - S. Mahayana (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
The long history of Malayan-Indonesia language often can’t be separated from many political interest of state. moreover, after juridical legitimated in UUD 1945 as State Language, Indonesian language act as state language, national language, union language, official language, interrelation language in every side of people. Therefore, Indonesian language become un-separated part of Indonesian nation’s life. Meanwhile, because Indonesian language rooted from Malayan language, an effort to unite similarity with language in ASEAN (south East Asia) region, as Malaysia, Singapore, and Brunei Darussalam language, isn’t a meaningless task. In fact, to prevent misunderstanding between nations, this effort is a necessary.